Implementation of ISO 14001 Standard by World Trade Organization (WTO) Based on Technical Barriers to Trade (TBT) Agreement and Its Practices in Indonesia - Ferdi, Ferdi (Indonesian Journal of International Law, 2024)
The implementation of the ISO 14001 standard by the World Trade Organization (WTO) has been regulated in the Technical Barriers to Trade (TBT) Agreement (Annex 1A WTO). ISO 14001 is an Environmental Management Standard (EMS) issued by the International Organization for Standardization (ISO). ISO is one of the organizations that determine the international standard. The standard set by ISO has been utilized to equalize the standard of the WTO members in world trade (Preamble TBT Agreement). The WTO is an international organization regulating world trade to ensure it flows smoothly. TBT oversees that the technical regulations and standards, including packaging, marking and labelling requirements, and procedures for assessment of conformity with technical regulations and standards do not create unnecessary obstacles to international trade. One of the standards ISO sets in world trade is ISO 14001, the Environmental Management System (EMS). The WTO has decided that the EMS standard is one of the requirements for goods and services to be traded internationally. Several developing countries of the WTO members consider EMS a breach of the TBT Agreement conducted by developed countries. Export demands using ISO 14001 are considered to be contrary to the non-discrimination principle of the WTO free trade system, as EMS is merely a non-compulsory standard regulated as a mandatory trade requirement by developed countries. Indonesia as a member of both ISO and the WTO has had its own record in implementing the policies of these organizations. This article will discuss the practice of ISO 14001 in the member states of the WTO, including Indonesia as sample of it implementation.